From an imagined community to genuine communities: Birth and development of Etrimo Apartment Buildings in Brussels, 1950–2020 - Courbebaisse, Audrey (2022)
Using an analysis of apartment buildings built in Brussels by the real estate developer Etrimo between 1950 and 1970, we investigate the ability of collective housing to build and support an inhabitants’ community. After World War II, Etrimo took advantage of the poor state of existing housing stock and the return of Belgian families from Congo to intensify its production of apartment buildings for aspiring middle-class homeowners. These buildings consisted of repeated, identical three-room dwellings offering all modern comforts for the nuclear family of the thirty-year post-war boom. The portrait of this family, reflected in various commercial brochures and the 14,000 dwellings built in Brussels by the private developer, suggests a relatively homogeneous middle class. How did this imagined, abstract community materialise? First, we present how the juxtaposition of identical households may or may not have produced a homogenous community at the project’s different spatial scales. This analysis is based on primary sources at our disposal: sales brochures, Etrimo advertisement posters, writings by the company’s founder Jean-François Collin on the legal and financial set-up of his business, plans of the housing units and complexes. Second, on the basis of interviews with inhabitants and on-site observations of living practices in the collective spaces of the housing estates, we highlight the model Etrimo housing estates offers contemporary society for new ways of living together.